2018
DOI: 10.1101/475624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deriving Cardiomyocytes from Human Amniocytes

Abstract: STATEMENTAmniocytes are a possible source of patient-specific cardiomyocytes for newborns with congenital heart disease. Genome-wide DNA methylation patterns and transcriptional repressors preclude direct differentiation, but pluripotent reprogramming provides cardiomyocytes for dissecting genetic pathways contributing to this disease. ABSTRACTMany forms of congenital heart disease (CHD) have high morbidity-mortality rates and require challenging surgeries. Human amniocytes have important stem cell characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…It has been reported that amniotic epithelial cells contain progenitor cells or resident cardiac stem cells that differentiate into various organs such as the heart, brain, and kidney [ 16 ]. These resident cardiac stem cells in AF have been studied for the expression of transcription factors of mesodermal origin, such as NKx 2-5 , GATA-4 , and the TBX family, which play an essential role in heart development during embryogenesis [ 17 , 18 ]. Thus, any defects in the functional properties of these cardiac stem cells or cardiac progenitor stem cells will contribute to an increased risk of neonatal heart defects as in the case of ICHDs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that amniotic epithelial cells contain progenitor cells or resident cardiac stem cells that differentiate into various organs such as the heart, brain, and kidney [ 16 ]. These resident cardiac stem cells in AF have been studied for the expression of transcription factors of mesodermal origin, such as NKx 2-5 , GATA-4 , and the TBX family, which play an essential role in heart development during embryogenesis [ 17 , 18 ]. Thus, any defects in the functional properties of these cardiac stem cells or cardiac progenitor stem cells will contribute to an increased risk of neonatal heart defects as in the case of ICHDs.…”
Section: Introductionmentioning
confidence: 99%